Seizures in patients with acute pesticide intoxication, with a focus on glufosinate ammonium. (April 2018) - Park, S; Kim, DE; Park, SY; Gil, HW; Hong, SY
The incidence and clinical aspects of seizures remain to be elucidated in patients with acute pesticide intoxication. The present study included subjects who ingested pesticide with the intention of committing suicide and were treated at Soonchunhyang University Hospital (Cheonan, Korea) between January 2011 and December 2014. We analyzed the incidence and characterized the type and frequency of seizure, from the medical records of 464 patients with acute pesticide intoxication, according to the pesticide class. The effect of seizure on the clinical outcome was assessed. The incidence of seizure was 31.5% in patients who ingested glufosinate ammonium 2-amino-4-[hydroxyl (methyl) phosphinoyl] butyrate; ammonium DL-homoalanin-4-yl (methyl) phosphinate, followed by those who ingested pyrethroid (5.9%) or glycine derivatives (5.4%). All of the seizures developed between 12 and 24 h of pesticide ingestion and had ceased by 72 h after seizure initiation, following treatment with antiseizure medication. Generalized tonic–clonic seizures were the most commonly observed (85.7% of the cases). Multivariable logistic regression analysis showed that the effect of seizure on mortality was not statistically significant. In conclusion, glufosinate ammonium herbicide is the most common seizurogenic pesticide class. Seizure itself was not a risk factor for mortality in patients with acute glufosinate ammonium intoxication.